1966
DOI: 10.1039/df9664100149
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemisorption in simple catalytic reactions

Abstract: Hydrogen and oxygen sorption and their interaction have been studied on evaporated films of Pt, Pd, Rh, Ni, Fey Mo, Cu and Mn. Hydrogenation of cyclopropane has been followed on films of Ni, and sorption and interaction of hydrogen and nitrogen have been measured on films of Fe. Oxygen adsorbed on nickel does not react at 78°K with hydrogen adsorbed subsequently, but restricts the hydrogen adsorption roughly proportional to the degree of the surface coverage by oxygen. At room temperature there is extensive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1970
1970
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…According to Ponee et al 71 the reaction between hydrogen and oxygen at the Pd surface at 0 °C goes to completion producing desorbable water, in agreement with the last step, reaction (39d), ofthe four-step mechanism (39). However, according to Lundstrom et af.,33 the details of the waterproduction reactions on the palladium layer are still not known.…”
Section: R13mentioning
confidence: 61%
“…According to Ponee et al 71 the reaction between hydrogen and oxygen at the Pd surface at 0 °C goes to completion producing desorbable water, in agreement with the last step, reaction (39d), ofthe four-step mechanism (39). However, according to Lundstrom et af.,33 the details of the waterproduction reactions on the palladium layer are still not known.…”
Section: R13mentioning
confidence: 61%
“…During the growth process, divalent ions of carbon impurity are supposed to replace trivalent cations of Al, which leads to the formation of hole‐trapping centers 5 . It had been reported that hydrogen has a strong decarbonizing effect at high temperatures, 12 and the divalent carbon ions in the crystal decrease after annealing in H 2 , which leads to a decline in absorption coefficient at 206 nm. Moreover, the carbon in the as‐grown crystal volatilizes in the form of CO or CO 2 after annealing in air; hence, the crystal that was first annealed in air and then in hydrogen shows a very low absorption coefficient at 206 and 256 nm.…”
Section: Resultsmentioning
confidence: 99%
“…They agreed, from their results, as Roberts [19], Beeck and Ritchie [20] and other authors [21], that hydrogen atom was localized on a surface metallic atom. Some authors, as Ponec et al [22], on the base of this conclusion, proposed that, by the measure of the quantity of chemisorbed hydrogen, the area determination of the surface atoms could be possible. It was the first time that surface atoms and their coverage by adsorbed species was taken in consideration.…”
Section: Exchange Reactions: C-h Bond Ruptures Are Involvedmentioning
confidence: 95%
“…These functions (equations (22) and (23)) were only dependent on the thermodynamics of hydrogen chemisorption and on the number Z of potential sites involved in the chemisorption process of the hydrocarbon. The values for Z were found between 7±2 and 8±2 for methane [34] and ethane [48] chemisorption on rhodium, respectively.…”
Section: On the Structure And Demanding Character Of Catalytic Reactimentioning
confidence: 99%